A coupled phase diagram experimental study and thermodynamic optimization of the Li2O-CaO-Al2O3 and Li2O-CaO-SiO2 systems, and prediction of the phase diagrams of the Li2O-CaO-Al2O3-SiO2 system. Issue 5 (May 2020) - Konar, Bikram; Jung, In-Ho
Abstract: A coupled experimental phase diagram study and thermodynamic modeling of the Li2 O-CaO-Al2 O3 and Li2 O-CaO-SiO2 systems was conducted at 1 atm total pressure. Differential scanning calorimetry (DSC) measurements were performed in the Li2 O-CaO-Al2 O3 and Li2 O-CaO-SiO2 systems. In addition, the phase relations in the Li2 O-CaO-Al2 O3 system were determined by equilibration/quenching experiments at 1643 and 1743 K, and the phases were characterized with X-ray diffraction (XRD) and Electron-probe micro analysis-wavelength dispersive spectroscopy (EPMA-WDS). The absence of ternary compounds or solid solutions was confirmed. Congruent melting of Li2 CaSiO4 compound in the Li2 O-CaO-SiO2 system was determined at 1350 ± 5 K. Thermodynamic optimization of the Li2 O-CaO-Al2 O3 and Li2 O-CaO-SiO2 systems was carried out based on new phase diagram experiments and critically evaluated literature data. The phase diagrams of the quaternary Li2 O-CaO-Al2 O3 -SiO2 system were predicted using the thermodynamic models with optimized model parameters.